The Influence of the Gobak Sodor Traditional Game on Physical Fitness and Academic Achievement (Literature Study) - Sucipto, Adi; Kabau, Nanda; Sunuyeko, Nurcholis (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
Everyone, especially students, naturally desires a fit body and high academic achievement. These two things are also directly and closely related, as only students with physical fitness can achieve high academic results. To achieve both of these things, various efforts are needed, including sports activities, one form of which is playing the traditional game of gobak sodor. This research is a literature study that uses secondary data as its data source. Secondary data sources were obtained through documentation in the form of national journals (accessed via Google Scholar) and international journals (accessed via SCOPUS/ScienceDirect) using the PRISMA search flow. The criteria for journal articles used as data sources were those published in the past five years (2019-2023). Through the PRISMA flow, 40 journal articles were selected (35 national journals, 5 international journals). The data analysis techniques used are annotated bibliography analysis and percentage analysis. The results of the review and analysis of the selected journal articles indicate the following conclusions: (1) There is a significant positive influence of the traditional game gobak sodor on physical fitness, with 88% of the selected journal articles supporting this conclusion; (2) There is a significant positive influence of the traditional game gobak sodor on academic achievement, with 96% of the selected journal articles supporting this conclusion.